1985
DOI: 10.1037/0278-6133.4.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Components of Type A, hostility, and anger-in: Further relationships to angiographic findings.

Abstract: In a previous study of patients undergoing angiography at Duke University Medical Center, we reported that of all components of the Type A behavior pattern (TABP), only Potential for Hostility and Anger-In were significantly associated with extent of coronary artery disease (CAD). The present study was undertaken to replicate these findings using a different patient population. Tape-recorded structured interviews from 125 angiography patients at Massachusetts General Hospital were blind scored using the compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
0
3

Year Published

1985
1985
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(89 citation statements)
references
References 22 publications
7
79
0
3
Order By: Relevance
“…Later studies however have found that the hostility/anger items of the Type A/B scales both differentiate between these personality types (Rosenman, Rahe, Borhani, & Feinleib, 1976;Chesney, Black, Chadwick, & Rosenman, 1981) Dembroski, Dimsdale and Hackett (1985) found that Global TABP (substantially correlated with explosiveness of speech, rapid-acce1erated speech and response latency) was completely unrelated to the severity of coronary artery disease. In this study, anger-in was the strongest predictor of CHD, and these results were consistent with an earlier study (Dembroski et al, 1985) in which potential for CHD was predictive only for those individuals who did notexpress their hostility openly. Anger-in was also found to be predictive of the incidence of CHD morbidity and mortality in both men and women in the Framingham population (Haynes et al, 1980).…”
Section: Cardiovascular Reactivitymentioning
confidence: 99%
“…Later studies however have found that the hostility/anger items of the Type A/B scales both differentiate between these personality types (Rosenman, Rahe, Borhani, & Feinleib, 1976;Chesney, Black, Chadwick, & Rosenman, 1981) Dembroski, Dimsdale and Hackett (1985) found that Global TABP (substantially correlated with explosiveness of speech, rapid-acce1erated speech and response latency) was completely unrelated to the severity of coronary artery disease. In this study, anger-in was the strongest predictor of CHD, and these results were consistent with an earlier study (Dembroski et al, 1985) in which potential for CHD was predictive only for those individuals who did notexpress their hostility openly. Anger-in was also found to be predictive of the incidence of CHD morbidity and mortality in both men and women in the Framingham population (Haynes et al, 1980).…”
Section: Cardiovascular Reactivitymentioning
confidence: 99%
“…Tests showed that, above all, hostility and anger were components that were significantly related to cardiovascular disease in both sexes [29] . These findings, however, must be interpreted cautiously as many of the studies are methodologically weak.…”
Section: Clinical Perspectives 1759mentioning
confidence: 99%
“…Aunque para ser más exactos, deberíamos hablar del componente irahostilidad del PCTA (Barefoot et al, 1983;Dembroski et al, 1989;Hecker, Chesney, Black, & Frautschi, 1988;King, 1997;MacDougall, Dembroski, Dimsdale, & Hackett, 1985;Richter et al, 2011;Shekelle et al, 1983;Williams et al, 1980). En general, existe una gran confusión entre los términos ira y hostilidad, siendo éstos en ocasiones empleados como sinónimos, sin serlo; en el siguiente apartado, se detallará más a este respecto.…”
Section: A12 El Constructo Ira-hostilidad El Nuevo Patrón De Predunclassified
“…A grandes rasgos, los resultados obtenidos con este tipo de trabajos siguen la misma tónica que acabamos de comentar. Esto es, existe una variedad de estudios en los que se encuentra una relación positiva entre la hostilidad y el grado de oclusión coronaria (Arrowood, Uhirich, Gomillion, Popio, & Raft, 1982;MacDougall et al, 1985;Williams et al, 1980).…”
Section: A13 Relación Entre Hostilidad Y Ecunclassified
See 1 more Smart Citation